APPLICATION OF GROUP GUIDANCE TO IMPROVE SELF-CONFIDENCE AND LEARNING ACHIEVEMENT (Study in 8th grade at SMP Negeri 06 Lebong) - Zahlul Zahlul; Nina Kurniah (DIADIK, 2019)
This research is conducted to describe the increasing student’s self-confidence, student’s learning achievement, and the effectiveness of group guidance services for problem solving techniques in 8th grade students at SMPN 06 Lebong. This research was Class Action Research continued experimentation quasi. The subjects of this study were eighth graders of SMPN 06 Lebong. The Class Action Research subjects were students of class VIII.A, while the experiments for class VIII.B and the control  class were VIII.C. The instruments used are teacher activity observation sheets and test sheet for self-confidence and student achievement. The data analysis technique used percentage and t-test. The results of this study indicate that (1) the use of group guidance services for problem solving techniques could increase the students’ confident; (2) the use of group guidance services for problem solving techniques could increase the students’ achievements; (3) the effectiveness of group guidance services for problem solving techniques could students’ achievements eighth graders of SMPN 06 Lebong